Effect of attention bias modification on event‐related potentials in patients with irritable bowel syndrome: A preliminary brain function and psycho‐behavioral study. Issue 10 (30th July 2018) - Tayama, J.; Saigo, T.; Ogawa, S.; Takeoka, A.; Hamaguchi, T.; Inoue, K.; Okamura, H.; Yajima, J.; Matsudaira, K.; Fukudo, S.; Shirabe, S.
Abstract: Background: Attention bias modification normalizes electroencephalographic abnormalities in alpha and beta power percentages related to attention in patients with irritable bowel syndrome (IBS). Yet, it is unknown whether ABM contributes to the normalization of event‐related potentials (ERP) in these patients. We hypothesized that ERP related to attention deficit would be normalized after ABM implementation in individuals with IBS. Methods: Thirteen patients with IBS and 10 control subjects completed a 2‐month intervention that included five ABM sessions. Each session included 128 trials, resulting in a total of 640 trials during the study period. Event‐related potentials were measured at the first and fifth sessions. As per the international 10‐20 system for electroencephalographic electrode placement, right parietal P4 was evaluated to measure the attention component of facial expression processing. Key Results: A group comparison of P100 latency at P4 revealed that latencies were significantly different between groups in session 1 (IBS vs control, 108 ± 8 vs 97 ± 14; t = −2.51, P = .0203). This difference was absent in session 5 (94 ± 11 vs 93 ± 11, respectively; t = −0.397, P = .6954, r = .09), indicating an effect of ABM in the IBS group. Conclusions and inferences: Attention bias modification may have clinical utility for normalizing brain function and specifically attentional abnormalities in patients with IBS. Abstract : We hypothesized that ERP related to attention deficit would be normalized after attention bias modification (ABM) implementation in individuals with irritable bowel syndrome (IBS). Event‐related potentials were normalized after ABM and right parietal regions in the IBS group. Attention bias modification may have clinical utility for normalizing brain function and specifically attentional abnormalities in patients with IBS.